Characteristics of adults who stutter by treatments sought. (3rd July 2019) - Iverach, Lisa; Jones, Mark; Lowe, Robyn; O'Brian, Susan; Menzies, Ross G.; Packman, Ann; Onslow, Mark
Abstract: Several treatment approaches are available for adults who stutter, including speech treatment, cognitive behaviour therapy (CBT) treatment for anxiety, and a combination of both. It is useful to determine whether any differences exist between adults who stutter enrolled in different types of treatment. Therefore, the purpose of this study was to compare demographic, speech, and psychological characteristics of adults who stutter enrolled in speech, psychological, and combined treatment programs. Participants were 288 adults who stuttered (18–80 years) enrolled in one of three different treatment programs: Speech Treatment for stuttering ( n  = 134), Anxiety Treatment for anxiety about stuttering ( n  = 70), or Speech Treatment for Stuttering With or Without Anxiety Treatment ( n  = 84). Participants completed a range of demographic, speech, and psychological measures prior to the start of treatment. A significantly higher proportion of participants in the Anxiety Treatment group were in a personal relationship than the other treatment groups. The Anxiety Treatment group had higher average age than the other treatment groups. The Speech Treatment group also demonstrated significantly higher self-rated stuttering severity than the Anxiety Treatment group, even though there were no significant difference between groups for clinician-rated percentage of syllables stuttered. Although most characteristics of adults who stuttered did not vary by treatment type, the present findings suggest that adults who stutter enrolled in speech treatment perceived their stuttering as more severe, which may have prompted treatment seeking. Further research is needed regarding the supportive influence of personal relationship for those with the disorder.